Kritik Bermotif Dakwah atau Ghibah Terselubung? Telaah Etis Julid fī Sabīlillāh Berdasarkan Hadis - Fauzan Akbar (Yayasan Albahriah Jamiah Indonesia, 2025)
The phenomenon of julid fī Sabīlillāh, namely criticism wrapped in the intention of amar ma’ruf nahi munkar, often gives rise to the practice of backbiting which is prohibited in Islam. The background of this problem is rooted in the lack of public understanding of the boundaries of nahi munkar, as regulated in the hadith of the Prophet SAW. This study aims to identify when the practice of nahi munkar can shift into the sin of backbiting, as well as to provide ethical guidance based on hadith in carrying out amar ma’ruf nahi munkar correctly. The method used is qualitative with thematic analysis of hadiths related to nahi munkar and backbiting, as well as a case study of the phenomenon of communication on social media. The results of the study show that nahi munkar can turn into backbiting when criticism is carried out without fulfilling the requirements of sincerity, using non-constructive methods, or with the aim of demeaning others. The conclusion of this study emphasizes the importance of understanding the principles of Islamic ethics in julid fī sabīlillāh to avoid deviations such as backbiting. This study also provides practical recommendations for preaching in accordance with the teachings of the Prophet Muhammad, especially in the digital era.